The secondary structure of apolipoprotein A‐I on 9.6‐nm reconstituted high‐density lipoprotein determined by EPR spectroscopy. (10th June 2013) - Oda, Michael N.; Budamagunta, Madhu S.; Borja, Mark S.; Petrlova, Jitka; Voss, John C.; Lagerstedt, Jens O.
Abstract : Apolipoprotein A‐I (ApoA‐I) is the major protein component of high‐density lipoprotein (HDL), and is critical for maintenance of cholesterol homeostasis. During reverse cholesterol transport, HDL transitions between an array of subclasses, differing in size and composition. This process requires ApoA‐I to adapt to changes in the shape of the HDL particle, transiting from an apolipoprotein to a myriad of HDL subclass‐specific conformations. Changes in ApoA‐I structure cause alterations in HDL‐specific enzyme and receptor‐binding properties, and thereby direct the HDL particle through the reverse cholesterol transport pathway. In this study, we used site‐directed spin label spectroscopy to examine the conformational details of the ApoA‐I central domain on HDL. The motional dynamics and accessibility to hydrophobic/hydrophilic relaxation agents of ApoA‐I residues 99–163 on 9.6‐nm reconstituted HDL was analyzed by EPR. In previous analyses, we examined residues 6–98 and 164–238 (of ApoA‐I's 243 residues), and combining these findings with the current results, we have generated a full‐length map of the backbone structure of reconstituted HDL‐associated ApoA‐I. Remarkably, given that the majority of ApoA‐I's length is composed of amphipathic helices, we have identified nonhelical residues, specifically the presence of a β‐strand (residues 149–157). The significance of these nonhelical residues is discussed, along with the other features, in the context of ApoA‐I function in contrast to recent models derived by other methods. Abstract : Site‐directed spin label electron paramagnetic resonance (SDSL‐EPR) spectroscopy was used to examine the conformational details of the apolipoprotein A‐I (apoA‐I) central domain on high‐density lipoprotein (HDL). Combined with previous analyses a complete representation of secondary structure distribution apoA‐I on lipid‐bound 9.6‐nm rHDL in solution is depicted and compared to lipid‐free apoA‐I structure.